Artemisinic acid attenuates osteoclast formation and titanium particle-induced osteolysis via inhibition of RANKL-induced ROS accumulation and MAPK and NF-κB signaling pathways - Gao, Tian; Yu, Chaohong; Shi, Xiaofeng; Hu, Yuehao; Chang, Yongyun; Zhang, Jingwei; Wang, Yitian; Zhai, Zanjing; Jia, Xinlin; Mao, Yuanqing (Frontiers in Pharmacology, 2024)
Periprosthetic osteolysis (PPO) is the most common cause of joint arthroplasty failure. Its progression involves both biological and mechanical factors. Osteoclastogenesis induced by wear from debris-cell interactions, ultimately leading to excessive bone erosion, is considered the primary cause of PPO; therefore, targeting osteoclasts is a promising treatment approach. Currently available drugs have various side effects and limitations. Artemisinic acid (ArA) is a sesquiterpene isolated from the traditional herb Artemisia annua L. that has various pharmacological effects, such as antimalarial, anti-inflammatory, and antioxidant activities. Therefore, this study was aimed at investigating the effect of ArA on osteoclast formation and bone resorption function in vitro, as well as wear particle-induced osteolysis in vivo, and to explore its molecular mechanism of action. Here, we report that ArA inhibits RANKL-stimulated osteoclast formation and function. Mechanistically, ArA suppresses intracellular reactive oxygen species levels by activating the antioxidant response via nuclear factor erythroid-2-related factor 2 (Nrf2) pathway upregulation. It also inhibits the mitogen-activated kinases (MAPK) and nuclear factor-κB (NF-κB) pathways, as well as the transcription and expression of NFATc1 and c-Fos. In vivo experiments demonstrated that ArA reduces osteoclast formation and alleviates titanium particle-induced calvarial osteolysis. Collectively, our study highlights that ArA, with its osteoprotective and antioxidant effects, is a promising therapeutic agent for preventing and treating PPO and other osteoclast-mediated osteolytic diseases.